Growth, Blood Parameters, Immune Response and Antioxidant Enzyme Activities in Rainbow Trout (Oncorhynchus mykiss Walbaum, 1792) Fed Diets Supplemented with Fumitory (Fumaria officinalis) - FILOGH, Abdelsalam; BİLEN, Soner; SÖNMEZ, Adem Yavuz; ELP, Mahmut (Ankara University Faculty of Agriculture, 2023)
In a feeding experiment for 75 days, the effects of fumitory (Fumaria officinalis) extract on growth, haematology, immune response and antioxidant enzyme activities in rainbow trout (Oncorhynchus mykiss) were evaluated. The aqueous methanolic extract of the plant was mixed with feeds at three different levels, 0.1% (FO1), 0.2% (FO2) and 0.3% (FO3), and feed with no plant extract donated as the control. All four groups (mean initial weight: 13.02 ± 0.02 g) were fed with the prepared diets twice daily ad libitum in a triplicate experiment. Blood and liver samples were taken from the fish on 15, 30, 45, 60 and 75 days. Also, overall growth parameters were determined based on body weight data recorded from all fish before and at the end of feeding trial. Results indicated that there were variations in nonspecific immune parameters (lysozyme, myeloperoxidase and oxidative radical production), but supplementation of the plant extract did not affect the immune response of the fish significantly. On the other hand, there was a general increase in the antioxidant enzyme activities (superoxide dismutase, catalase, glutathione peroxidase, and glucose-6-phosphate dehydrogenase) evaluated in this study. Furthermore, possibly the most remarkable finding of the study is that the growth performance in the FO3 group was roughly 30% higher than that of the control group. Considering all findings in the present study, we conclude that 0.3% supplementation of fumitory extract would be beneficial for rainbow trout farming with respect to elevated growth and antioxidant status.
Keywords: feed additive; organic; Agriculture (General); Mühendislik; Growth promoter; Supplement; Organic; Medicinal plant; Feed additive; supplement; growth promoter; S1-972; Engineering; medicinal plant; 3. Good health; 14. Life underwater